Investigating The Effect Of Marketing Mix Through Motivation On Purchase Intention In Perumnas Griya Jetis Permai Mojokerto - PUSPITO, Atras Radifan; SHIRATINA, Aldina (PT Keberlanjutan Strategis Indonesia, 2023)
This research aims to examine the direct and indirect effects of Product, Price, Promotion, Place, and Motivation on Purchase Intention at Perumahan Griya Jetis Permai Mojokerto. The research sample consists of 255 respondents who are buyers that have gone through the marketing and sales process. Non-Probability Sampling method was used for data collection, employing a Likert scale questionnaire. The data analysis method used in this study is Partial Least Square-Structural Equation Modelling (PLS-SEM) through Outer Model, Inner Model, and Resampling Bootstrap. The results of the study show that Product, Price, Promotion, and Place have a positive and significant influence on Motivation. Motivation also has a positive and significant effect on Purchase Intention. Additionally, Product and Promotion have a positive and significant impact on Purchase Intention. However, Price and Place do not have a positive and significant effect on Purchase Intention. Overall, the research results indicate that Motivation plays a mediating role as an intervening variable between Product, Price, Promotion, and Place on Purchase Intention at Perumahan Griya Jetis Permai Mojokerto. The findings of this study can be used as a guide for Perumahan Griya Jetis Permai Mojokerto in designing effective marketing strategies to enhance Purchase Intention.